Cement degradation in CO2 storage sites: a review on potential applications of nanomaterials - Tiong, Michelle; Gholami, Raoof; Rahman, Muhammad Ekhlasur (SpringerOpen, 2018)
© 2018 The Author(s) Carbon capture and sequestration (CCS) has been employed to reduce global warming, which is one of the critical environmental issues gained the attention of scientific and industrial communities worldwide. Once implemented successfully, CCS can store at least 5 billion tons of CO2per year as an effective and technologically safe method. However, there have been a few issues raised in recent years, indicating the potential leakages paths created during and after injection. One of the major issues might be the chemical interaction of supercritical CO2with the cement, which may lead to the partial or total loss of the cement sheath. There have been many approaches presented to improve the physical and mechanical properties of the cement against CO2attack such as changing the water-to-cement ratio, employing pozzolanic materials, and considering non-Portland cements. However, a limited success has been reported to the application of these approaches once implemented in a real-field condition. To date, only a few studies reported the application of nanoparticles as sophisticated additives which can reinforce oil well cements. This paper provides a review on the possible application of nanomaterials in the cement industry where physical and mechanical characteristics of the cement can be modified to have a better resistance against corrosive environments such as CO2storage sites. The results obtained indicated that adding 0.5 wt% of Carbon NanoTubes (CNTs) and NanoGlass Flakes (NGFs) can reinforce the thermal stability and coating characteristics of the cement which are required to increase the chance of survival in a CO2sequestrated site. Nanosilica can also be a good choice and added to the cement by as much as 3.0 wt% to improve pozzolanic reactivity and thermal stability as per the reports of recent studies.